PH-Responsive benzaldehyde-functionalized PEG-based polymeric nanoparticles for drug delivery: Effect of preparation method on morphology, dye encapsulation and attachment. (5th February 2020) - Smyth, Peter; Gibson, Thomas J.; Irvine, Gavin; Black, Gemma; Lavery, Daniel; Semsarilar, Mona; Scott, Christopher J.; Themistou, Efrosyni
Graphical abstract: Highlights: pH responsive amphiphilic block copolymers were synthesized by RAFT polymerization. pH-switch and single emulsion-evaporation techniques enabled nanoparticle formation. Nanoparticles are both pH-responsive and non-cytotoxic. Functional benzaldehyde groups allowed site-directed conjugation at particle surface. Nanoparticles were able to encapsulate dyes and deliver payload to cells in vitro. Abstract: Functionalized, pH-responsive and biocompatible polymeric nanoparticles have attracted the interest of many researchers working on novel pharmaceutical formulations. Here, in an effort to develop an efficient drug delivery formulation, all these properties are combined in one polymeric nanoparticle system. More specifically, benzaldehyde-functionalized amphiphilic block copolymers based on PEG-based oligo(ethylene glycol) methacrylate (OEGMA), benzaldehyde-containing para -formyl phenyl methacrylate (pFPMA) and pH-responsive 2-(diisopropyl)aminoethyl methacrylate (DPA) monomers are readily prepared by reversible addition-fragmentation chain transfer (RAFT) polymerization. pH-Switch and single emulsion-solvent evaporation post-polymerization processing methods are used to prepare benzaldehyde-functionalized PEGylated pH-responsive nanoparticles with diameters of 180–230 nm. After nanoparticle formation, the benzaldehyde groups on the surface are shown to react with an Alexa Fluor 488 hydroxylamine dye through oxime bond formation, illustrating the potential for these particles to be surface-functionalized with biologically important molecules, such as fluorescent dyes for tracking their intracellular fate or antibodies for targeted therapy. Encapsulation of Nile Red and rhodamine 6G dyes is performed during the post-polymerization processing step for nanoparticle formation. Nanoparticles with a fluorescent cargo were shown to be successfully internalized in both A2780 ovarian cancer and A549 lung epithelial human cells in vitro, further illustrating the potential for these formulations to be used as triggered release therapeutic drug delivery vehicles.